The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1038/leu.2010.118
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of NF-κB target genes in MALT lymphoma with and without chromosome translocation: insights into molecular mechanism

Abstract: Mucosa-associated lymphoid tissue (MALT) lymphoma is characterized by t(11;18)(q21;q21)/API2-MALT1, t(1;14)(p22;q32)/ BCL10-IGH and t(14;18)(q32;q21)/IGH-MALT1, which commonly activate the nuclear factor (NF)-jB pathway. Gastric MALT lymphomas harboring such translocations usually do not respond to Helicobacter pylori eradication, while most of those without translocation can be cured by antibiotics. To understand the molecular mechanism of these different MALT lymphoma subgroups, we performed gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 38 publications
1
77
0
2
Order By: Relevance
“…Most of the KIF1Bβ-induced, DHX9-dependent targets were IFN-induced or IFN-related, consistent with earlier reports implicating DHX9 in transcriptional regulation of IFN-α-inducible genes ( 22 ). Some of these genes are known NF-κB downstream targets (23)(24)(25), in line with earlier observations demonstrating a DHX9-NF-κB interaction resulting in the transactivation of specific promoters ( 18 , 26 ). In addition, the proapoptotic XIAP-associated factor 1 ( XAF1 ) was identified ( Fig.…”
Section: Dhx9 Nuclear Localization Induced By Kif1bb Stimulates Proapsupporting
confidence: 91%
“…Most of the KIF1Bβ-induced, DHX9-dependent targets were IFN-induced or IFN-related, consistent with earlier reports implicating DHX9 in transcriptional regulation of IFN-α-inducible genes ( 22 ). Some of these genes are known NF-κB downstream targets (23)(24)(25), in line with earlier observations demonstrating a DHX9-NF-κB interaction resulting in the transactivation of specific promoters ( 18 , 26 ). In addition, the proapoptotic XIAP-associated factor 1 ( XAF1 ) was identified ( Fig.…”
Section: Dhx9 Nuclear Localization Induced By Kif1bb Stimulates Proapsupporting
confidence: 91%
“…2 To investigate whether A20 inactivation by mutation/deletion leads to enhanced NF-κB activities, we measured the expression of the above NF-κB target genes in 18 cases of OAML with A20 inactivating mutation and 17 cases without any evidence of A20, ABIN-1/2, MALT1 and IGH genetic abnormalities by quantitative RT-PCR. The expression of CCR2, TLR6 and BCL2, although not CD69, was significantly higher in cases with A20 mutation than those without A20 genetic abnormalities (Figure 2).…”
Section: A20 Inactivation Correlates With Increased Expression Of Nf-mentioning
confidence: 99%
“…1 By analyses of the gene expression profiles, we showed that the NF-κB target genes CCR2, TLR6, BCL2 and CD69 were highly expressed in MALT lymphoma with the above translocations. 2 The above translocations occur frequently in MALT lymphoma of the stomach and lung, but rarely in those of the ocular adnexa, salivary glands and thyroid. 1 By genomic profiling of translocation negative ocular adnexal MALT lymphoma (OAML), we and others identified A20 as the target of 6q23.3 deletion.…”
Section: Introductionmentioning
confidence: 99%
“…120 The t(11;18)(q21;q21) translocation is restricted to extranodal MALT lymphomas and has not been reported in other forms of marginal zone lymphoma, such as splenic or nodal, or in chronic gastritis associated with H pylori. 121,122 Gastric MALT lymphomas without t(11;18)(q21;q21) often exhibit aneuploidy, for example, trisomy 3, 12, or 18. 118, 119,123 The discovery of t(11;18)(q21;q21) in some patients with gastric MALT lymphoma has led to exciting clinical prognostic correlations.…”
Section: 110mentioning
confidence: 99%